2014
DOI: 10.3109/17483107.2014.974222
|View full text |Cite
|
Sign up to set email alerts
|

Eye gaze technology: a South African perspective

Abstract: Purpose: Based on the bioecological model by Bronfenbrenner, this paper will provide a broad perspective on factors that need to be taken into account in order to facilitate communication and participation in preliterate children making use of electronic AAC systems accessed through eye gaze.Method: Two case studies of children who have been provided with the technology described are presented. The case studies were analysed using the four nested systems of the ecology as a framework to describe not only the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 12 publications
0
29
0
Order By: Relevance
“…Teachers seem to acknowledge that students' intrinsic characteristics (i.e., body functions and structures, personal factors) may be quite stable and resistant to change. Focusing exclusively on these aspects reflects a deficitbased approach, situating the problem explanation within the individual rather than within the environment (Raghavendra et al, 2007;Van Niekerk & Tönsing, 2015;WHO, 2001). AAC and other role players), while one theme (student characteristics) incorporates both body functions and personal factors (WHO, 2001).…”
Section: Parentsmentioning
confidence: 99%
“…Teachers seem to acknowledge that students' intrinsic characteristics (i.e., body functions and structures, personal factors) may be quite stable and resistant to change. Focusing exclusively on these aspects reflects a deficitbased approach, situating the problem explanation within the individual rather than within the environment (Raghavendra et al, 2007;Van Niekerk & Tönsing, 2015;WHO, 2001). AAC and other role players), while one theme (student characteristics) incorporates both body functions and personal factors (WHO, 2001).…”
Section: Parentsmentioning
confidence: 99%
“…The availability and affordability of assistive technology such as aided AAC systems also influences AAC practice (Van Niekerk & Tönsing, 2015). Nonelectronic AAC systems are more frequently used in South African special schools than electronic AAC devices (Tönsing & Dada, 2016).…”
mentioning
confidence: 99%
“…Earlier research has shown that involving key persons such as parents and providing them with the knowledge and skills needed is in the long run essential to a sustained use of assistive technology [18,19]. The parents in this study received education on eye-gaze control technology and on how to support their child.…”
Section: Resultsmentioning
confidence: 99%